Reimagining Feminism in Beauty and the Beast: A Critical Analysis of Gender Roles and Power Dynamics - Sharenlie, Grania; Cai, Pei Yi; Djohan, Febrina Stevani; Chang, Gabrielle Angela; Surya, Michaella Isabel (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This research examines Vera Southgate “Beauty and The Beast” through the lenses of Feminist literary criticism. Focusing on how the story adresses traditional gender roles and transformation. Using Simone de Beauvoir to explore the role of women in society. As a result: 1) The narrative suppresses conventional evaluations by shifting focus from physical appearance to inner virtue and emotional transformation. Beast’s appearance does not fit societal expectations. It makes society, Beauty, does not accept the Beast by his physical appearance. 2) Traditional gender roles are actively imposed, marginalizing female agency and reinforcing patriarchal norms. The traditional gender roles between women and men in society are shown in this literature, where men are more dominant and providers while women are caretakers and submissive. 3) The interrelationship of power between characters illustrates a dialectical relationship in which dependence and autonomy are continuously renegotiated. True love is not based on physical appearance, but it is from the kindness from the heart. It can make a big transformation when someone finds their true love. This analysis is significant for its contribution to feminist literary criticism, as it illustrates the dual capacity of literature to both reinforce and challenge societal structures. It is expected that these insights will stimulate further research into the transformative potential of narrative in reshaping gender identities and power relations.